2022
DOI: 10.1155/2022/6947756
|View full text |Cite
|
Sign up to set email alerts
|

Novel PEEK Retentive Elements versus Conventional Retentive Elements in Mandibular Overdentures: A Randomized Controlled Trial

Abstract: Background. Many patients suffer from lack of retention of conventional mandibular overdentures due to loss of clip retention over time. Computer-aided design-computer-aided manufacturing (CAD-CAM) milled polyether ether ketone (PEEK) materials may be used for the construction of retentive housing and clips for improving retention of implant-supported overdentures. Objective. To compare retention and patient satisfaction of implant-supported mandibular overdentures retained by conventional nylon clip and metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…8 The impact of reconstructive digital dentistry on patient satisfaction as well as on the patients' oral health-related quality of life (OHRQoL) of the edentulous subjects who have undergone rehabilitation has recently been studied by a number of authors. 22,39 Relatively little information about the rehabilitation of edentulous patients using four implant-assisted mandibular overdenture with the recently developed and digitally constructed PEEK or PMMA base materials is available in the literature. Therefore, this study was developed to shed light on how these new base materials affect patient satisfaction and oral health-related quality of life (OHRQOL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The impact of reconstructive digital dentistry on patient satisfaction as well as on the patients' oral health-related quality of life (OHRQoL) of the edentulous subjects who have undergone rehabilitation has recently been studied by a number of authors. 22,39 Relatively little information about the rehabilitation of edentulous patients using four implant-assisted mandibular overdenture with the recently developed and digitally constructed PEEK or PMMA base materials is available in the literature. Therefore, this study was developed to shed light on how these new base materials affect patient satisfaction and oral health-related quality of life (OHRQOL).…”
Section: Discussionmentioning
confidence: 99%
“…38 PEEK retentive material enhanced patient satisfaction by offering greater retention than did traditional material. 39 It is important to identify patient satisfaction with overdenture base materials and to assess oral problems difference between them. Such identification may enhance denture acceptance, consequently improving patient well-being and quality of life.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some clinical studies have used PEEK to help retain implant-supported overdentures. Sharaf et al [ 92 ] designed novel PEEK-retentive elements in mandibular overdentures and measured the retention and patient satisfaction compared to metal housings and nylon-retentive elements. The author stated that PEEK provided more retention than conventional materials and that it led to improved patient satisfaction.…”
Section: Clinical Performance For Removable Peek Prosthodonticsmentioning
confidence: 99%
“…41,42 Some studies have shown that PEEK can be employed as an overdenture attachment retainer. [43][44][45][46] PEEK can be fabricated using either CAD/CAM or injection molding.…”
Section: Introductionmentioning
confidence: 99%